FAILURE MODE AND EFFECTS ANALYSIS OF SHIP SYSTEMS USING AN INTEGRATED DEMPSTER SHAFER THEORY AND ELECTRE METHOD - Emovon, Ikuobase (Journal of Advanced Manufacturing Technology (JAMT), 2016)
Failure Mode and Effects Analysis (FMEA) is a risk analysis tool which is used to define, identify, and eliminate known and/or potential failures from a system. The task is generally performed by team of experts. Each of the team of experts can express diverse opinions in rating of failure modes of systems which may be in the form of precise data and imprecise distribution ratings. However the RPN of FMEA is incapable of using these various forms of information in the prioritisation of risk of failure modes. This is one of the main limitations of FMEA. Furthermore the technique is limited to the use of three decision criteria thereby excluding other important decision criteria such as production loss in prioritising risk. To address these problems a novel FMEA tool is proposed which combines Dempster Shafer Theory with the ELECTRE method to provide a more efficient failure mode prioritisation method. With this technique the Dempster Shafer Theory is used in aggregating different failure mode ratings from experts and the ELECTRE method is applied in the ranking of failure modes. The applicability of the proposed technique is demonstrated with a case study of a marine diesel engine. Results showed that the proposed method can be applied in addressing risk prioritisation problem more efficiently than the FMEA and its variant.